Effectiveness of Norethisterone Acetate alone Versus in Combination with Letrozole for treatment of Chronic Pelvic Chronic Pain and Dyspareunia in Patients with Endometriosis - Saima Ashraf, Arooj Fatimah Khosa, Rahat Farwa (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare mean chronic pelvic pain (CPP) and deep dyspareunia intensity after 6 month treatment of using norethisterone acetate alone and combination with letrozole in patients with endometriosis. Study design & duration: This randomized controlled trail was conducted from February 1st, 2020 to January 31st, 2021. Setting: Department of Obs. &Gynecology, Nishtar hospital Multan. Materials and methods: Seventy two women with age range 18-60 years regardless of parity, having endometriosis with baseline pain > 5 at visual analogue scale were included in study. Pain was measured on VAS at baseline and after 6 months of treatment. All data was entered in a pre-designed proforma. Results: Mean age of cases was 39.83 ± 12.61 years in group-A and 41.58 ± 12.66 years in group-B. At baseline the mean chronic pelvic pain in group-A was 7.17 ± 1.28 and in group-B was 7.00 ± 1.39. The mean chronic pelvic pain at 6th month was statistically lower in group-A (1.72 ± 0.74) when compared with group-B (4.39 ± 0.64) with a p-value < 0.001. Similarly, deep dyspareunia was markedly reduced follow-up in both group A and group B at 6 months. Conclusion: CPP and deep dyspareunia are significantly reduced after 6 month of treatment with combined oral letrozole (2.5 mg/day) and norethisterone acetate (2.5 mg/day).